STRATEGI PETANI DALAM PEMASARAN SALAK DENGAN E-COMMERCE (PERDAGANGAN BERBASIS ELEKTRONIK) - Putra, Yosua Kon (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
Srumdude Subdistrict is a sub-district with the flagship of Salak commodity with a production of 554,310 KW and continues to increase annually, but there is a problem related to the marketing of the agricultural products, Salak price is not optimal and tends to the harvest. The purpose of this research is to know the strategy of farmers in marketing through e-commerce by specifying segmentation (geographic and demographic) targeting (value, volume, product, price, promotion and distribution) and posisitioning (STP) as well as know Salak business strategy using SWOT analysis. The implementation of this study was held in the month of February until July 2019 in Srumdude village, Srumdude District, Magelang Regency, Central Java. Research is done with a descriptive analysis method. The sampling location is purposive and samples were taken using the Harry King Nomogram. Based on the results of the study shows the implementation of marketing strategy only reaches 36.48% and SWOT analysis shows the strategy that can be applied, namely marketing development through e-commerce and exhibitions, product development into partnerships and Pressing the input cost.